Racial heteroidentification committees for admission to federal universities - Batista, Neusa Chaves (2020)
The article analyzes the racial quota policy for access to higher education in a Brazilian federal university in its most recent adjustment: the implementation of a racial heteroidentification committee whose decision is based on the phenotype of the candidates. The epistemological and methodological basis starts from a critical analysis of the policy, understanding that the construction of this public action is the result of clashes and disputes between actors who have different conceptions of social justice. The result of the research points out that, in the studied university, the implementation of the heteroidentification committee has significantly reduced, since the implementation of the racial quota, in 2008, the access of self-declared black people, indicating that the commissions call into question the meaning of what it is to be a black person in Brazil.